Practices of Dynamic Collaboration A Dialogical Approach to Strengthening Collaborative Intelligence in Teams - De Visch, Jan; Laske, Otto (Management for Professionals, 2020)
XXIII, 221 p. 27 illus., 26 illus. in color.